Transsphenoidal surgery and diabetes mellitus: An analysis of inpatient data and complications. (3rd February 2015) - Pines, Morgan J.; Raikundalia, Milap D.; Svider, Peter F.; Baredes, Soly; Liu, James K.; Eloy, Jean Anderson
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Transsphenoidal surgery (TSS) has emerged as the standard approach for pituitary resection due to its minimally invasive nature. There has been little analysis examining the impact of diabetes mellitus (DM) on patients undergoing TSS. In this study, we characterize DM's association with postoperative TSS complications. In addition to analysis of associated charges and patient demographics, we performed comparison of complication rates between DM and non‐DM patients who have undergone TSS in recent years. Methods The Nationwide Inpatient Sample, a database encompassing nearly 8 million inpatient hospitalizations, was evaluated for patients undergoing TSS from 2002 to 2010. Results Of 12, 938 TSS patients, 2, 173 (16.8%) had a DM diagnosis. The non‐DM cohort was younger (50.1 y ± 16.6SD vs. 56.8 y ± 14.1; P < 0.001) and had shorter hospitalizations and lesser charges. DM patients had a greater incidence of pulmonary, cardiac, urinary/renal, and fluid/electrolyte complications, and had a lesser incidence of diabetes insipidus (P < 0.05). Upon controlling for age, the greater incidence of pulmonary and fluid/electrolyte complications was present only among patients < 60 years of age. Higher occurrence of cerebrospinal fluid rhinorrhea was noted among black diabetics when compared to non‐DM blacks. Conclusions DM is associated with greater length of stay and hospital charges among TSS patients. DM patients undergoing TSS have a significantly greater incidence of pulmonary and fluid/electrolyte complications among patients under the age of 60, and greater risk for urinary/renal complications across all ages. Despite a theoretical concern due to an impaired wound‐healing in DM patients, association with cerebrospinal fluid rhinorrhea was only noted among black diabetics. Level of Evidence 2C. Laryngoscope, 125:2273–2279, 2015